The morphology of biblical Greek - Mounce, William D., 1953- (Zondervan Pub. House, 1998)
The Morphology of Biblical Greek explains, in a way second-year Greek students can understand, how Greek words are formed. It shows that Greek word formation follows a limited set of rules. Once these rules are understood, it becomes clear that forms which once seemed to be irregular or an exception actually follow these morphological rules. The Morphology of Biblical Greek has five parts: 1.The rules that determine how Greek words change. 2. The rules of verb formation, from augment to personal ending. 3. Paradigms for every type of noun and adjective form, with all the words that belong in each category and any peculiarities of a given word. 4. All the verbs and principal parts, with verbs that follow the same rules grouped together. 5. An index of all words in the New Testament with their morphological category. The Morphology of Biblical Greek contains the most complete set of paradigms for nouns, verbs, adjectives, and pronouns available for New Testament Greek.